The need for a unified ethical stance on child genital cutting - Earp, BD; Shahvisi, A; Reis-Dennis, S; Reis, E (SAGE Publications, 2021)
The American College of Nurse-Midwives, American Society for Pain Management Nursing, American Academy of Pediatrics, and other largely US-based medical organizations have argued that at least some forms of non-therapeutic child genital cutting, including routine penile circumcision, are ethically permissible even when performed on non-consenting minors. In support of this view, these organizations have at times appealed to potential health benefits that may follow from removing sexually sensitive, non-diseased tissue from the genitals of such minors. We argue that these appeals to "health benefits" as a way of justifying medically unnecessary child genital cutting practices may have unintended consequences. For example, it may create a "loophole" through which certain forms of female genital cutting-or female genital "mutilation" as it is defined by the World Health Organization-could potentially be legitimized. Moreover, by comparing current dominant Western attitudes toward female genital "mutilation" and so-called intersex genital "normalization" surgeries (i.e. surgeries on children with certain differences of sex development), we show that the concept of health invoked in each case is inconsistent and culturally biased. It is time for Western healthcare organizations-including the American College of Nurse-Midwives, American Society for Pain Management Nursing, American Academy of Pediatrics, and World Health Organization-to adopt a more consistent concept of health and a unified ethical stance when it comes to child genital cutting practices.